Budaya Konten Instan dan Karakteristik Belajar Generasi Alpha: Telaah terhadap Narasi Lost Generation di Era Digital - Dina Awaliyah Nurrohmah; Sofia Zaeti Nur Siregar; M Daffa Isnan Effendi; Abdul Fadhil (Advances In Education Journal, 2026)
This study aims to examine the relationship between instant-content culture and the learning characteristics of Alpha Generation in the digital era, as well as its relevance to the emerging lost generation narrative. This research employed a qualitative literature review method by analyzing relevant national and international scholarly publications on Alpha Generation, digital media, social media use, digital literacy, and learning processes. The findings indicate that the widespread consumption of short-form content through digital platforms encourages fast, visual, and practical learning habits among Alpha Generation students. However, excessive exposure may reduce attention span, learning concentration, and critical and reflective thinking skills. The study also reveals that the lost generation narrative cannot be accepted uncritically, as Alpha Generation possesses strong technological adaptability and digital creativity. Therefore, digital literacy development, parental supervision, and critical-thinking-oriented learning are essential to maximize the benefits of technology while minimizing its educational risks.